Science class is too hard: Perceived difficulty, disengagement, and the role of teacher autonomy support from a daily diary perspective. (December 2018) - Patall, Erika A.; Hooper, Sophia; Vasquez, Ariana C.; Pituch, Keenan A.; Steingut, Rebecca R.
Abstract: The current research aimed to investigate students' daily experiences in high school classes by answering the following questions: to what extent does daily perceived difficulty of science classwork predict daily feelings of competence and disengagement? Are autonomy-supportive teaching strategies useful when work in science class is perceived to be more difficult than the average day? Two-hundred and eighteen high school students in 43 science classes participated in the daily diary study across a six-week instructional unit. Results of multilevel modeling revealed that on days when students perceived their science classwork to be more difficult than usual, they experienced a decrease in perceived competence, which was in turn associated with an increase in disengagement. In addition, the current research suggested that the decrease in perceived competence and subsequent decrease in engagement as a function of perceived difficulty was minimized when students perceived their teachers to provide autonomy support. Discussion centers on the theoretical and practical implications. Highlights: Daily perceived difficulty in science predicts decreased perceived competence. Daily perceived competence mediates difficulty-disengagement relationship. Perceived teacher autonomy support mitigates negative correlates of difficulty.